Effect of Furnish on Temperature and Vapor Pressure Behavior in the Center of Mat Panels during Hot Pressing - Muhammad Navis Rofii; Noriko Yamamoto; Yoichi Kojima; Shigehiko Suzuki (Institute for Research and Community Services (LPPM) ITB, 2014)
Particleboard achieves its overall performance characteristics during hot pressing process. As this process is influenced by several factors, particularly temperature and pressure, it is very important to understand the behavior of both. This study investigates the effects of furnish materials on temperature and vapor pressure behavior inside particleboard mat panels during hot pressing. Strand type particles from hinoki and ring-flaker recycled wood particles were used as furnish for laboratory-scale particleboard panels with a target density of 0.76 g/cm³. Mat panels with a moisture content of about 10% were hot pressed at a platen temperature of 180°C and an initial pressure of 3 MPa until the mat center reached the same temperature as the platen. A press monitoring device (PressMAN Lite) was used for detecting the temperature and vapor pressure change in the center of the mat panels. The study showed that the furnish type affected the temperature and vapor behavior inside the mat panels. Particleboard made of hinoki strand resulted in a longer plateau time, a higher plateau temperature and a higher gas pressure generated during hot pressing than those of ring-flaker recycled wood particles. Mixed board resulted in values between those of the two other furnish materials.